2021
DOI: 10.1259/dmfr.20200417
|View full text |Cite|
|
Sign up to set email alerts
|

Do various imaging modalities provide potential early detection and diagnosis of medication-related osteonecrosis of the jaw? A review

Abstract: Objective: Patients with medication-related osteonecrosis of the jaw (MRONJ) often visit their dentists at advanced stages and subsequently require treatments that greatly affect quality of life. Currently, no clear diagnostic criteria exist to assess MRONJ, and the definitive diagnosis solely relies on clinical bone exposure. This ambiguity leads to a diagnostic delay, complications, and unnecessary burden. This article aims to identify imaging modalities’ usage and findings of MRONJ to provide possible appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 111 publications
0
14
0
2
Order By: Relevance
“…The role of three‐dimensional (3D) diagnostics in the detection of necrotic changes without exposed or probable bone (corresponding to AAOMS stage 0) has been addressed by working groups for some time (Wongratwanich et al, 2021). These patients present with non‐specific symptoms that cannot be attributed to dental causation.…”
Section: Introductionmentioning
confidence: 99%
“…The role of three‐dimensional (3D) diagnostics in the detection of necrotic changes without exposed or probable bone (corresponding to AAOMS stage 0) has been addressed by working groups for some time (Wongratwanich et al, 2021). These patients present with non‐specific symptoms that cannot be attributed to dental causation.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are confirmed by a recent review describing panoramic radiographs to be sufficient in depicting osteolysis, osteosclerosis, and thickened lamina dura, but the CBCT and CT can show more features unique to MRONJ, such as periosteal reaction and bone-within-bone appearance. Wongratwanich et al concluded that there is no consensus regarding the use of a specific imaging modality; therefore, dental practitioners should select the imaging modality according to the patient’s conditions to avoid over-investigation and unnecessary interventions [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pathognomonic imaging features for MRONJ have not been established 34 . Before computed tomography (CT) was available, panoramic radiographs were the sole means of diagnosis and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Before computed tomography (CT) was available, panoramic radiographs were the sole means of diagnosis and prognosis. CT is superior to panoramic radiographs because the necrosis level of the cortex bone, trabecular bone density, and sequestration position can be determined accurately 21 , 34 . However, compared to CT, panoramic radiographs offer lower costs, which is beneficial for periodic follow-up.…”
Section: Discussionmentioning
confidence: 99%